Jet Erosion Device (JEd) – measurement of soil erodibility coefficients - Ibrahim, Saerahany Legori; Ariffin, Junaidah; Abdullah, Jazuri; Muhamad, Noor Safwan (Penerbit Universiti Teknologi Malaysia, 2016)
Erosion from riverbank is most properly represented by the erodibility factor. One of the methods that can be used for in situ soil erodibility testing is the submerged jet test called Jet Erosion Test (JET). In this study, a newly modified version of the JET device namely Jet Erosion Device (JEd) is fabricated, with improved features and design that facilitates testing in the field and the laboratory. Analysis and calibration of the JEd tests were conducted to check on the reliability and performance of the Jet Erosion Device (JEd). Some preliminary results were shown to give some insights on the capabilities of the JEd. An evaluation of the erosion performance index i.e. jet index was performed to characterize the erosion resistance. The estimation of erodibility coefficients were made using the results of jet index obtained.